Designing a Network of Battery Swap Stations for Supporting UAVs in Long-range Delivery Operations - Ghaharikermani, Amirali; Parsa, Payam; Pohl, Edward A. (International Journal of Supply Chain Management, 2020)
Recently, the use of Unmanned Aerial Vehicle (UAV) for delivery services has become a topic of interest and research for large commercial service providers such as Google and Amazon. The delivery speed of UAVs provides such companies with a significant advantage in their market. Although utilizing the UAVs in product delivery has received tremendous excitement, several issues need to be resolved prior to real-world implementation. The first issue with using UAVs as a transportation mode is their limited flying range. Small UAVs are not able to fly long distances due to their limited battery life. Flight range can be improved by using battery swapping stations in the planning horizon. UAVs can replace their depleted batteries at these stations and continue their fights. In our research, we attempt to develop a model to construct a network of such stations in order to enable the UAVs to fly long distances for making deliveries to far-reaching demand points. In addition, we develop a Tabu-Search heuristic to solve several instances of the proposed problem.